In India, Study of the Impact of Tourism on Economic Development - Dr. Manan Kaushal (International Journal of Engineering and Management Research, 2018)
The tourism industry is a significant social phenomenon in practically every civilization, owing to the underlying human desire to have new and unique experiences in the areas of adventure, learning, and entertainment. Furthermore, tourism is influenced by a variety of elements, including socio-cultural, religious, and business activity. Tourism is fueled in part by the innate human need to learn about unexplored corners of the planet. Advances in technology, improvements in the knowledge domain, the construction of tourist-friendly facilities, transportation advancements, and the lowering of communication obstacles have all contributed to the tourism industry's growth in recent decades. As a result, it is widely recognized that tourism can play an important role in attaining inclusive and long-term growth and development. In most countries around the world, travel and tourism is a significant economic activity. Indirect and induced effects of the sector are important. Since a few years, the Indian tourist business has been rapidly expanding, demonstrating a large potential for creating jobs, earning foreign cash, and boosting the economy.